Knowledge and practices regarding antenatal care and factors associated with practice among pregnant mothers attending antenatal clinics in the Nallur MOH Area - Mahalingam, R.; Kamalarupan, L.; Surenthirakumaran, R. (University of Jaffna, 2020)
Antenatal care refers to the care women receive throughout pregnancy in order to ensure the wellbeing of both mother and baby. Good maternal knowledge and practices regarding antenatal care are necessary to improve pregnancy outcomes. This study was conducted to assess the knowledge and practices regarding antenatal care and the factors influencing antenatal care practices among pregnant mothers attending antenatal clinics in the Nallur MOH Area.
Keywords: Antenatal Care; Pregnant Mothers; Knowledge; Practice; Nallur